Inhaled nitric oxide therapy in preterm infants born before 34 weeks of gestation: a nationwide multicenter study - Rui-hua Ba; Lian Wang; Sheng-qian Huang; Bao-ying Feng; Mu-lin Yao; Jing Zhang; Yao Zhu; Guo-bao Liang; Zhi Zheng; Ling Liu; Qiu-fen Wei; Li Ma; et al. (Italian Journal of Pediatrics)
Abstract Background Despite the lack of consensus, the use of inhaled nitric oxide (iNO) in preterm infants with a gestational age (GA) of less than 34 weeks has been increasing in recent years. At present, there are no multi-center studies in China on the use of iNO in this population. This study aims to investigate the use of iNO in preterm infants under 34 weeks of gestation over the past 10 years in China, and provides evidence-based medical proof for the use of iNO in these neonates. Methods Using a retrospective study method, clinical data were collected from infants with a GA of less than 34 weeks who received iNO therapy in the neonatal units of five tertiary hospitals in China from January 2013 to December 2022. The infants were divided into two groups: Group A (2013–2017) and Group B (2018–2022). The differences in clinical characteristics, iNO use, and short-term outcomes between the two groups were analyzed. Results Over the past decade, the use of iNO in preterm infants with a GA of less than 34 weeks has increased gradually, with a more pronounced rise in its use among preterm infants born at 24–27 weeks. The proportion of infants receiving iNO therapy has increased from 1.23% (Group A) to 2.62% (Group B). Compared to Group A, the infants in Group B who received iNO therapy had a smaller GA and lower birth weight. The initial and maximum doses of iNO in Group B were higher (10.0 ppm vs. 8.0 ppm, 15.0 ppm vs. 9.0 ppm). More than half of the extremely preterm infants (EPI) and extremely low birth weight infants (ELBWI) died in both groups. In preterm infants with a GA of 32–33 weeks who were treated with iNO, the case fatality rate was significantly lower in Group B compared to Group A (9.1% vs. 28.2%). Conclusion The use of iNO in preterm infants with a GA of < 34 weeks has increased over the past 10 years. The treatment strategy for iNO has become more aggressive, and the observed reduction in mortality among relatively older preterm infants (32–33 weeks GA) may be linked to increased iNO utilization and higher dosing regimens. Notably, the case fatality rate among EPI and ELBWI remains elevated throughout the study period, with no statistically significant differences observed between the two groups. Given the benefits and risks of iNO therapy, routine use in EPI and ELBWI may not be advisable. Trial registration This article is a retrospective registered study, registered under the number ChiCTR2200066935 on December 21, 2022.